(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the use of geodetic methods in land surveying in the "Qirq kiz" massif of Ellikkala district of the Republic of Karakalpakstan. The study reveals the importance of modern geodetic technologies - GNSS receivers, total stations, remote sensing using drones and GIS programs. Based on practical observations, the effectiveness, accuracy and role of these technologies in land cadastre work and legal registration are highlighted. Also, proposals have been developed for the modernization of the cadastre system and the rational use of land resources. The results of the study provide scientific and practical foundations that can be used to improve the land management system at the republican level.